2021
DOI: 10.1021/acs.iecr.1c03019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Infinite Dilution Molar Conductivity for Unconventional Ions: A Quantitative Structure–Property Relationship Study

Abstract: The infinite dilution molar conductivity (λB ∞) that represents the interactions between ions and solvent molecules is an important transfer property for the utilization of ionic liquids (ILs) in electrochemical applications. However, employing the quantitative structure–property relationship (QSPR) model to predict the λB ∞ of unconventional ions remains to be explored. In this work, new λB ∞-QSPR models were developed to predict the λB ∞ of ions in aqueous solutions by using multiple linear regression (MLR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The key to constructing a QSPR model is to choose a set of suitable descriptors that are also unique, which can indicate the structural characteristics of cations and anions. This study used work by Song et al 42 to divide the charge density distribution area of cations and anions into certain intervals S σi (e•nm −2 ) as the descriptors to develop the λ-QSPR model. Table 1 shows the σ profiles of cations divided into 5 intervals, concentrating at −2.0−0.5 e•nm −2 .…”
Section: Dataset Of Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The key to constructing a QSPR model is to choose a set of suitable descriptors that are also unique, which can indicate the structural characteristics of cations and anions. This study used work by Song et al 42 to divide the charge density distribution area of cations and anions into certain intervals S σi (e•nm −2 ) as the descriptors to develop the λ-QSPR model. Table 1 shows the σ profiles of cations divided into 5 intervals, concentrating at −2.0−0.5 e•nm −2 .…”
Section: Dataset Of Thermal Conductivitymentioning
confidence: 99%
“…The second is that the fragment area descriptor obtained by COSMO-SAC in the work can distinguish the isomers of substances. In recent studies, QSPR models showed accurate predictions for the infinite dilution molar conductivity and infinite dilution diffusion coefficient of ILs developed based on fragment charge density distributions obtained using the COSMO-SAC model. , The reason for selecting the COSMO-SAC model is that it can generate the charge density distribution’s profile, namely, σ profiles that are called molecular fingerprints, which are identical to the human fingerprints and are unique . Moreover, the fragment charge density distributions separated by various intervals are unique.…”
Section: Introductionmentioning
confidence: 99%
“… 11 13 In QSPR, the quantitative relationship among the physicochemical properties, biological properties, and molecular structures of compounds is explored with various statistical methods and mathematical models. 14 , 15 Usually, the molecular descriptors were selected as inputs of the models. 16 In previous studies, the main methods used in the QSPR model include multivariable linear regression (MLR), artificial neural network (ANN), Gaussian process (GP), and support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%
“…To replace traditional mechanistic models, many researchers turned to the quantitative structure–property relationship (QSPR) model. In QSPR, the quantitative relationship among the physicochemical properties, biological properties, and molecular structures of compounds is explored with various statistical methods and mathematical models. , Usually, the molecular descriptors were selected as inputs of the models . In previous studies, the main methods used in the QSPR model include multivariable linear regression (MLR), artificial neural network (ANN), Gaussian process (GP), and support vector machine (SVM). , However, the complex correlation between molecular descriptors and high-dimensional nonlinear data required for dissolution prediction poses great difficulties in traditional machine learning methods …”
Section: Introductionmentioning
confidence: 99%
“…The COSMO-SAC model can be used to obtain the charge density distribution (σ-profile) and cavity volume ( V COSMO ). The charge density distribution area of molecules in a specific interval ( S σ i ) obtained from the σ-profile can be used as a structural descriptor reflecting the interactions, and the obtained V COSMO can be used as a structural descriptor reflecting the size of the molecular volume. ,, Consequently, a unique set of descriptors for the molecular structure can be obtained directly from the molecular structure.…”
Section: Introductionmentioning
confidence: 99%